Pelatihan Tata Kelola Keuangan Wirausahaan pada Santri PPM Tebu Falah - Lutfia, Citra; Djasuli, Mohamad; Harwida, Gita Arasy (PT. Karya Inovatif Nusantara, 2024)
Students who want to become entrepreneurs need to understand how to manage their business finances. Financial reporting serves as a valuable tool in assessing the financial performance of a business. It can point out potential problems, as well as decision-making that drives business growth. Many students have difficulty documenting financial reports clearly, in detail, and systematically when starting a business. To overcome this, this activity aims to provide insight related to entrepreneurial financial management to the students of Pondok Pesantren Mahasiswa (PPM) Tebu Falah, so that students are able to make simple accounting records and produce financial reports. The training material focuses on accounting records and financial reporting, through the use of a combination of 3 exposure methods, namely: lectures, tutorials, and discussions. Through this training, students will gain additional skills in making simple accounting records and producing financial reports as expected.